ANALISA YURIDIS HAK KEBEBASAN BERPENDAPAT BERDASARKAN KETENTUAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Suwito, Eddy (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2020)
The development of technology that continues to grow, the public increasingly facilitates socialization through technology. Opinion on free and uncontrolled social media causes harm to others. The law sees this phenomenon subsequently changing. Legal Information Known as Information and Electronic Transaction Law or ITE Law. However, the ITE Law cannot protect the entire general public. Because it is an Article in the ITE Law that is contrary to Article in the 1945 Constitution of the Republic of Indonesia.